Posttranslational modification of differentially expressed mitochondrial proteins in the retina during early experimental autoimmune uveitis - Saraswathy, Sindhu (Molecular Vision, 2011)
PURPOSE: Posttranslational modification of proteins plays an important role in cellular functions and is a key event in signal transduction pathways leading to oxidative stress and DNA damage. In this study, we used matrix-assisted laser desorption/ionization- time of flight (MALDI-TOF) to investigate the posttranslational modifications of the differentially expressed proteins in the retinal mitochondria during early experimental autoimmune uveitis (EAU). METHODS: EAU was induced in 18 B10RIII mice with 25 µg of inter-photoreceptor retinoid-binding protein (IRBP) emulsified with complete Freund’s adjuvant (CFA); 18 mice treated with CFA without IRBP served as controls. Retinas were removed from the experimental and control groups on day 7 post immunization; mitochondrial fractions were extracted and subjected to 2 dimentional-difference in gel electrophoresis (2D-DIGE); and the protein spots indicating differential expression were subjected to MALDI-TOF for protein identification and indication of any posttranslational modifications. RESULTS: Of the 13 proteins found to be differentially expressed by 2D-DIGE (including upregulated aconitase, mitochondrial heat shock protein (mtHsp) 70, lamin-1, syntaxin-binding protein, αA crystallin, βB2 crystallin, along with downregulated guanine nucleotide-binding protein and ATP synthase) nine were found to undergo posttranslational modification. Oxidation was a common modification found to occur on aconitase, mtHsp 70, ATP synthase, lamin-1, βB2-crystallin, guanine nucleotide-binding protein, and manganese superoxide dismutase (MnSOD). In addition, aconitase hydratase, mtHsp 70, guanine nucleotide-binding protein, ATP synthase, syntaxin-binding protein, βB2-crystallin, and lamin-1 were also modified by carbamidomethylation. αA-crystallin had a pyro-glu modification. CONCLUSIONS: Several proteins present in the retinal mitochondria are posttranslationally modified during early EAU, indicating the presence of oxidative stress and mitochondrial DNA damage. The most common modifications are oxidation and carbamidomethylation. A better understanding of the proteins susceptible to posttranslational modifications in the mitochondria at the early stage of the disease may serve to advance therapeutic interventions to attenuate disease progression.